Postępowanie karne przeciwko cudzoziemcowi w świetle badań empirycznych: [Criminal proceeding against a foreigner in the light of empirical studies] (Studia Prawnicze / The Legal Studies, 1990)
Dzięki odpowiedniemu stosowaniu przepisów o biegłych organ procesowy może powołać w charakterze tłumacza każdą osobę dającą gwarancję odpowiedniego przekładu, o ile brak podstaw do jej wyłączenia. Nie znaczy to jednak, że brak merytorycznych przesłanek do postulowania swoistego "preferowania" tłumaczy przysięgłych (sądowych).Powstaje pytanie, czy organ jest zobowiązany zapewnić osobie nie znającej języka polskiego przekład na jej język ojczysty, czy też zamiast tego na inny język, którym się ona posługuje. Mimo milczenia ustawy w tej kwestii wydaje się, że tę drugą formę tłumaczenia można, moim zdaniem, dopuścić, pod warunkiem uzyskania przez organ od oskarżonego wyraźnego oświadczenia odnośnie zarówno znajomość języka nieojczystego, jak i zgody na tłumaczenie na ten język.„Prawo do tłumacza” w świetle orzecznictwa Europejskiego Trybunału Praw Człowieka przysługuje każdemu oskarżonemu bezpłatnie, a zatem bez względu na jego sytuację materialną. Oznacza to zakaz obciążania go jakimikolwiek kosztami wynikającymi z tłumaczenia dokumentów procesowych oraz udziału tłumacza w postępowaniu. Tymczasem zgodnie z art. 547 § 1 k.p.k. sąd zasądza na rzecz Skarbu Państwa koszty postępowania włącznie z wydatkami poniesionymi w toku postępowania przygotowawczego. Art. 554 § 2 k.p.k. dodaje, że do kosztów postępowania wlicza się m.in. należności tłumaczy.Zawiadomienia o tymczasowym aresztowaniu dotyczy zarówno przepis „szczególny” z art. 539 k.p.k., jak i przepisy ogólne, dotyczące ogółu aresztowanych (art. 220 i 221 k.p.k.). Te dwie grupy przepisów nie wyłączają się nawzajem, co oznacza, że zwłaszcza art. 220 k.p.k. powinien być stosowany także w stosunku do oskarżonych i podejrzanych-cudzoziemców. Przy niewyłączonym działaniu art. 220 § 2 k.p.k., obywatel państwa, o którym mowa w art. 541 § 2 k.p.k., może wskazać osobę, którą organ stosujący tymczasowe aresztowanie winien o tym fakcie zawiadomić. W konsekwencji należy, moim zdaniem, przyjąć, że zastosowanie art. 539 mogłoby zostać wyłączone, gdyby adresatem zawiadomienia w takiej sytuacji miał być urząd konsularny lub dyplomatyczny; natomiast jeśli aresztowany cudzoziemiec wskaże konkretną osobę, podając jej nazwisko i adres, to należy ją zawiadomić - nawet w sytuacji określonej w art. 541 § 2 i nawet gdy jest nią urzędnik konsularny czy pracownik obcego przedstawicielstwa. Thanks to the appropriate application of the regulations on experts, the proceeding authority may appoint any person offering a guarantee of an adequate translation as an interpreter, provided that there are no grounds for their exclusion. This does not mean, however, that there is no substantive reason to postulate a kind of “preference” for sworn (court) interpreters.A question arises whether the authority is obliged to provide a person who does not speak Polish with a translation into his or her mother tongue, or instead into another language spoken by said person. Despite the silence of the law on this issue, it seems that this second form of translation may, in my opinion, be allowed, provided that the authority obtains an explicit statement from the accused regarding both knowledge of the non-native language and consent to translation into that language.“The right to an interpreter”, in the light of the judicial decisions of the European Court of Human Rights is granted to every accused person free of charge and therefore regardless of his or her financial situation. This means that any costs arising from the translation of procedural documents and the interpreter's participation in the proceedings cannot be charged to the accused. Meanwhile, pursuant to Article 547(1) of the Code of Criminal Proceeding, the court orders the State Treasury to cover the costs of the proceeding, including expenses made during the preparatory proceeding. Article 554(2) of the Code of Criminal Proceeding adds that the costs of the proceedings include, inter alia, the fees of the interpreters.Notifications of temporary detention are covered by both the “special” provision of Article 539 of the Code of Criminal Proceeding and the general provisions which apply to detainees in general (Articles 220 and 221 of the Code of Criminal Proceeding). These two groups of regulations are not mutually excluding, which means that especially Article 220 of the Code of Criminal Proceeding should be applied also to accused and suspects - foreigners. With the unexcluded application of Article 220(2) of the Code of Criminal Proceeding, a citizen of the state referred to in Article 541(2) of the Code of Criminal Proceeding may designate a person to be notified by the authority applying the measure of temporary detention. Consequently, I believe it should be assumed that the application of Article 539 could be excluded if the recipient of the notification in such a situation were to be a consular or a diplomatic office; on the other hand, if the arrested foreign national indicates a specific person, giving his or her name and address, that person must be notified - even in the situation referred to in Article 541(2) and even if it is a consular officer or an employee of a foreign representative authority.